2011
DOI: 10.1068/a43354
|View full text |Cite
|
Sign up to set email alerts
|

Passing Propinquities in the Multicultural City: The Everyday Encounters of Bus Passengering

Abstract: This paper examines how intercultural relations are continuously developed, destroyed, and remade in the practice of everyday bus travel. Through an ethnographic study of one bus route across Birmingham, UK, the paper explores the formation of relational practices on the move and the bodily orientations, public codes of conduct, material cultures, habits and affects through which they are formed. In particular, this paper gives specific attention to the tacit obligations of public travel and how such obligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
243
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 63 publications
(65 reference statements)
0
243
0
Order By: Relevance
“…This focus on the oft-neglected possibilities of tolerance presents both an alternative and a challenge to the metanarratives that have typically characterised much of the debate concerning its value. Whilst recent attention to the geographies of tolerance has begun to highlight the political possibilities of tolerance as a value (Gill et al, 2012), there is still much more to be said about its taking place (Wilson, 2011). For example, Gill et al (2012) demonstrate how tolerance as a pragmatic practice can provide "a dual space of recognition and disagreement" (page 511) and thus the "necessary condition for a functioning politics" (page 510).…”
Section: The Possibilities Of Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…This focus on the oft-neglected possibilities of tolerance presents both an alternative and a challenge to the metanarratives that have typically characterised much of the debate concerning its value. Whilst recent attention to the geographies of tolerance has begun to highlight the political possibilities of tolerance as a value (Gill et al, 2012), there is still much more to be said about its taking place (Wilson, 2011). For example, Gill et al (2012) demonstrate how tolerance as a pragmatic practice can provide "a dual space of recognition and disagreement" (page 511) and thus the "necessary condition for a functioning politics" (page 510).…”
Section: The Possibilities Of Tolerancementioning
confidence: 99%
“…This work has fed into two linked projects, the first of which was focused on ordinary spaces of tolerance (see also Wilson, 2011;2013a;2013b), and the second of which is focused on programmes of community intervention. With an international network including branches across North America, the UK, and Europe, the organisation aims to tackle prejudice and conflict through workshop events tailored to meet the requirements of different groups, communities, and organisations.…”
Section: Tolerance Dialogue and Conflict Transformationmentioning
confidence: 99%
“…It is an issue that is particularly pertinent given rising levels of insecurity generated by post 9/11 terrorism and the current global financial crisis because in times of trouble attitudes towards minorities tend to harden. Given the implicit role of shared space in providing the opportunity for positive encounters between strangers, geography, urban studies and planning have paid increasing attention to this question, notwithstanding the longstanding interest of social psychologists in ÔcontactÕ theory (Allport 1954, Hewstone and Brown 1986) Here, some authors have observed the potential for ÔdifferenceÕ to be dissolved through a process of mixing and hybridisation of culture as a result of everyday encounters and interactions in public spaces (such as in cafes, on buses, at community events and sports clubs) where there is an accommodation of otherness because the proximity of strangers necessitates a pragmatic engagement across categorical boundaries (Amin 2002, Laurier & Philo 2006, Noble 2009, Wise 2009, Wilson 2011. Drawing on examples from a range of studies of hospitality spaces Bell (2007: 19) argues that food and eating create a feeling of being involved with others, providing consumers with a license to talk to each other which can facilitate positive encounters such that commensality Ôcan Ébe about social identification, the sharing of not only food and drink but also world views and patterns of livingÕ.…”
Section: Reflections On Geographies Of Encountermentioning
confidence: 99%
“…This is evident through recent writings about cosmopolitanism, hospitality and new urban citizenship (e.g. Amin 2002, Bell 2007, Binnie et al 2006, Laurier & Philo 2006a/b, Iveson 2006, Wilson 2011.…”
mentioning
confidence: 99%
See 1 more Smart Citation